Serum soluble TWEAK levels in non-alcoholic fatty liver disease (Annals of Medical Research, 2021)
Aim: Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease. The exact pathogenesis of NAFLD has not been fully elucidated. Tumor necrosis factor-like weak inducer of apoptosis (TWEAK) is a member of TNF superfamily and it has been implicated in the pathogenesis of several diseases including liver inflammation and fibrosis. Current study was conducted to evaluate serum sTWEAK levels in patients with NAFLD.Material and Methods: Seventeen patients with biopsy proven non-alcoholic steatohepatitis (NASH), 22 patients with simple hepatosteatosis and 30 healthy controls were included in the study and serum sTWEAK concentrations were measured using commercial ELISA kits.Results: Mean serum sTWEAK concentration was significantly lower in the NASH group when compared to the simple hepatosteatosis group and healthy controls (199.6±101.2 pg/mL, 246.1±65.7 pg/mL and 277.6±117.6 pg/mL respectively, p=0.029). ROC analyses for sTWEAK to differentiate NASH patients from healthy controls and from simple hepatosteatosis revealed that AUC for sTWEAK was 0.712 (%95 CI, 0.543-0.880). For the specified cut off value, 171.1 pg/mL positive and negative predictive values calculated were 64.3% and 85.5% respectively. Conclusion: Serum sTWEAK concentration is decreasedin patients with NASH when compared to patients with simple hepatosteatosis and healthy controls. Keywords: Nonalcoholic steatohepatitis; tumor necrosis factor-like weak inducer of apoptosis; sTWEAK; ﬁbroblast growth factor-inducible 14; Fn 14.
Keywords: Nonalcoholic steatohepatitis; tumor necrosis factor-like weak inducer of apoptosis; sTWEAK; ﬁbroblast growth factor-inducible 14; Fn 14.